Effects of Experimental Terrestrialization on the Skin Mucus Proteome of African Lungfish (Protopterus dolloi) - Heimroth, Ryan D.; Casadei, Elisa; Salinas, Irene (Frontiers in Immunology, 2018)
Animal mucosal barriers constantly interact with the external environment and this interaction is markedly different in aquatic and terrestrial environments. Transitioning from water to land was a critical step in vertebrate evolution but the immune adaptations that mucosal barriers such as the skin underwent during that process are essentially unknown. Vertebrate animals such as the African lungfish have a bimodal life, switching from freshwater to terrestrial habitats when environmental conditions are not favorable. African lungfish skin mucus secretions contribute to the terrestrialization process by forming a cocoon that surrounds and protect the lungfish body. The goal of this study is to characterize the skin mucus immunoproteome of African lungfish, Protopterus dolloi, before and during the induction phase of terrestrialization as well as the immunoproteome of the gill mucus during the terrestrialization induction phase. Using LC-MS/MS, we identified a total of 974 proteins using a lungfish Illumina RNA-seq database, 1256 proteins from previously published lungfish Sequence Read Archive (SRA) and 880 proteins using a lungfish 454 RNA-seq database for annotation in the three samples analyzed (free-swimming skin mucus, terrestrialized skin mucus and terrestrialized gill mucus). The terrestrialized skin mucus proteome was enriched in proteins with known antimicrobial functions such as histones and S100 proteins compared to free-swimming skin mucus. In support, gene ontology analyses showed that the terrestrialized skin mucus proteome has predicted functions in processes such as viral process, defense response to Gram negative bacterium and tumor necrosis factor mediated signaling. Importantly, we observed a switch in immunoglobulin heavy chain secretion upon terrestrialization, with IgW1L and IgM1 present in free-swimming skin mucus and IgW1L, IgM1 and IgM2 in terrestrialized skin mucus. Combined, these results indicate an increase investment in the production of unique immune molecules in P. dolloi skin mucus in response to terrestrialization that likely better protect lungfish against external aggressors found in land.